Engaging Black Churches to Address Cancer Health Disparities: Project CHURCH - McNeill, Lorna H.; Reitzel, Lorraine R.; Escoto, Kamisha H.; Roberson, Crystal L.; Nguyen, Nga; Vidrine, Jennifer I.; Strong, Larkin L.; Wetter, David W. (Frontiers in Public Health, 2018)
African Americans in the United States suffer disproportionately from cancer, having the highest mortality rate of any racial/ethnic group across all cancers for the past several decades. In addition, significant disparities exist in several cancer risk behaviors, including obesity, intake of fruits and vegetables, leisure time physical activity and cancer screening. Addressing these disparities require successful development of relationships with minority communities to partner in the research process, in order to understand areas of critical need and develop interventions that are compatible with this community. In this manuscript we describe Project CHURCH (Creating a Higher Understanding of Cancer Research and Community Health), a collaborative partnership between The University of Texas MD Anderson Cancer Center and Houston-area African American churches. Project CHURCH was developed to understand disparities in cancer prevention risk factors and engage African Americans as partners in the research process. Using community-based participatory research principles, we describe the development and infrastructure of the research partnership, as well as how the church community has been engaged in the development and implementation of a large African American cohort study (N = 2,338). Finally, the characteristics of the cohort are presented along with cohort success in addressing community need while having significant contribution to the scientific literature. Project CHURCH serves as a valuable resource for cancer prevention in the African American community.